Välfärdsfantasier: Personalisering av offentlig service i Storbritannien - West, Karen; Lundgren, Anna Sofia (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2015)
The article shows how personalisation in the UK has become part of a particular public service reform trajectory, in which it is argued that the threat of an ageing population makes it imperative to transform public services if the welfare state is not to collapse the welfare state. Personalisation is also the means by which it is thought that public service users can be empowered to make individual choices. The article describes the concrete emergence of a personalisation model and focuses then on the fantasmatic dimension of the ideology of personalisation in order to account for its grip to date. This requires more than a simply deconstructive critique of policy ideas but an examination of the co-construction of and libidinal investment in social projects.